Psychometric Analysis of Young's Internet Addiction Test among High School Students of North India. - Karol, Sunidhi; Thakare, Meenal M.; Giri, Purushottam A.; Karol, Mohit; Sharma, Minnat; Dhiman, Rishab (Indian Journal of Community Medicine)
Background: Internet addiction is a serious problem that can negatively impact both the physical and mental health of adolescents. The Internet Addiction Test (IAT) is the most commonly used instrument to screen internet addiction worldwide. The study investigated the psychometric properties of the Hindi version of young's IAT. School-based, descriptive, cross-sectional study design. Methods and Materials: The Hindi version of the IAT questionnaire was used to estimate internet addiction. Factor structure was analyzed by exploratory (EFA) and confirmatory factor (CFA) analyses, whereas reliability was measured with Cronbach's alpha coefficient. EFA, CFA, MANOVA, and logistic regression model. Results: Factor analysis revealed that the Hindi version of IAT consisted of a two-factor model, and had good validity (χ2 P < 0.000; RMSEA = 0.039; CFI = 0.969; SRMR = 0.031). Cronbach's alpha score was 0.92. A significant association was also observed between the level of internet addiction with the duration of internet use per day (P < 0.05). Conclusions: The Hindi version of IAT provides good validity and reliability in a two-factor model. Therefore, it can be utilized as a tool for screening internet addiction in the Hindi-speaking population of India.